Physicochemical Properties and Mineral Compositions of Pawpaw and Watermelon Seed Oils - Adaramola, Banji; Onigbinde, Adebayo (Pakistan Journal of Nutrition, 2015)
The physicochemical properties and mineral contents of ripe and unripe pawpaw and water melon seed oils were evaluated. The physicochemical evaluation showed that the oils have low saponification, low iodine, low peroxide and low acid values. These values indicated that the oils have good commercial values and uses apart from their nutritional values and can also be stored for a long period of time. The assay of mineral contents also showed that the oils contained useful macro and micro nutrients especially high amount of phosphorous which suggests that it can be used to treat hypophosphatemia. The ripe and unripe seed oils have almost the same physicochemical properties which suggest that the oil can be harvested when the pawpaw is ripe or otherwise. The three seed oils have more long chain saturated fatty acid (moderate saponification value) which makes them good oils for soap making. Also their calorific values are high enough to make them a good source of bio-fuels. The oils should be evaluated for toxicological effect before it is recommended for human consumption and its melting point and flash point also be evaluated to know its grade as a biofuel.